The impact of the COVID-19 pandemic on the activities of small enterprises on the example of business customers of a manufacturing company - Danielak Wiesław (Management)
The aim of the article is to show the impact of the COVID-19 pandemic on the activities of small enterprises on the example of business customers of a manufacturing company. The article contains current issues and presents problems regarding the global pandemic caused by COVID-19. which started in March 2020. The theoretical part shows the impact of the pandemic crisis on the activities of enterprises. The empirical part presents the results of research showing the decisions of company managers during the COVID-19 pandemic affecting the behavior of employees. suppliers. customers and the paper producer. The results of the research can be a source of knowledge for top and middle management. but also for employees whose safety of life and health is particularly important in the times of the COVID-19 pandemic.